KNOWLEDGE TRANSFER KESENIAN RANDAI UNIT PECINTA BUDAYA MINANGKABAU UNIVERSITAS PADJADJARAN - Nurul Husna Zalmi, Fadhila; Zalmi, Fathonah Az Zahra (UIN Imam Bonjol Padang, 2021)
ABSTRACT Traditional culture is increasingly less attractive to the public due to modernization, and one form of culture that is forgotten is traditional art, because this is an important regional traditional art to be preserved. In UPBM art activities, especially randai, knowledge transfer is carried out by the older generation as the knowledge owner to the younger generation as the recipient of knowledge. The purpose of this study was to determine the knowledge transfer activities in the art of randai at UPBM Unpad. The research method used is an approach by describing the process of knowledge sharing activities in the art of randai at UPBM. The data of this research was obtained through observation of UPBM Unpad randai arts activities. The result of this research is the transfer process in UPBM Unpad randai arts activities seen through SECI Nonaka theory, namely socialization, externalization, combination, and internalization. Keywords: knowledge transfer, Minangkabau culture, randai, Minangkabau Culture Lovers Unit (UPBM) ABSTRAK Kebudayaan tradisional semakin lama semakin kurang diminati oleh masyarakat yang disebabkan oleh modernisasi, dan salah satu bentuk kebudayaan yang mulai terlupakan tersebut adalah kesenian tradisional, karena hal inilah kesenian tradisional daerah penting untuk dilestarikan. Dalam kegiatan kesenian UPBM khususnya randai, knowledge transfer dilakukan oleh angkatan yang lebih tua sebagai pemilik pengetahuan kepada angkatan yang lebih muda sebagai penerima pengetahuan. Tujuan dari penelitian ini adalah untuk mengetahui kegiatan knowledge transfer pada kesenian randai di UPBM Unpad. Metode penelitian yang digunakan adalah pendekatan kualitatif dengan mendeksripsikan proses kegiatan knowledge sharing pada kesenian randai di UPBM. Data penelitian ini diperoleh melalui observasi kegiatan kesenian randai UPBM Unpad. Hasil dari penelitian ini adalah terjadinya proses transfer pengetahuan dalam kegiatan kesenian randai UPBM Unpad dilihat melalui teori SECI Nonaka yaitu sosialiasi, eksternalisasi, kombinasi, dan internalisasi. Keywords: knowledge transfer, Minangkabau culture, randai, Minangkabau Culture Lovers Unit (UPBM)